OPTIMALISASI PENDIDIKAN KARAKTER ANAK USIA DINI MELALUI SENTRA BERMAIN PERAN DI PAUD LAB SCHOOL IKIP PGRI JEMBER - Eky Prasetya Pertiwi; Ianatuz - Zahro (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2019)
Character education is a necessity because education does not only make students smarter, but also has to have character and manners so that its existence as a member of society becomes meaningful to itself. Ages 5-6 years need to be introduced about values about good and bad, right and wrong from an early age. This is expected so that what has been introduced to children from an early age can be embedded and attached until the child grows and develops in the next stage. The form of teaching in forming a good person is one of them with character education. Character education needs to be optimized. One way to optimize character education is through role playing centers. This study aims to optimize character education in early childhood through role playing centers. Data is collected through observation, field notes, interviews, and documentation. This research is a type of classroom action research. This research was carried out collaboratively between principals, class teachers and researchers. The action aims to improve the character values of children through role play centers. Research activities include: planning, implementing, collecting data and analyzing information data. This research was conducted at an early childhood education institution at PAUD Lab School Ikip Pgri Jember. The results of the study found that role playing centers can be used as an effort to optimize character education for early childhood through: Habitual understanding of behavior in role playing, The emergence of Self Awareness in Children in Role Playing, Understanding of Dialogues about Character Values.